Solve for x: -4(x - 2) - (x - 1) < -156

-4(x - 2) - (x - 1) -165/-5 x > 33

Question

Asked 8/27/2012 11:39:13 PM

Updated 12/15/2015 4:41:48 AM

3 Answers/Comments

Edited by Andrew. [12/15/2015 4:40:52 AM]

f
freestar.config.enabled_slots.push({ placementName: 'weegy_incontent_1', slotId: 'weegy_incontent_1' });

Rating

8

-4(x - 2) - (x - 1) < -156

-4x + 8 - x + 1 < -156

-5x + 9 < -156

-5x < -156 - 9

-5x < - 165

x > -165/-5

x > 33

-4x + 8 - x + 1 < -156

-5x + 9 < -156

-5x < -156 - 9

-5x < - 165

x > -165/-5

x > 33

Added 12/15/2015 4:41:48 AM

This answer has been confirmed as correct and helpful.

Solve for x: -3x - 2 = 10 **Weegy:** 2(-3x + 5) = 22,
-6x + 10 = 22,
-6x = 12,
x = 12/-6,
x = -2
(More)

Question

Updated 8/15/2014 9:45:30 AM

1 Answer/Comment

Solve for x: 5( x + 1) - 3( x - 1) > -9 **Weegy:** (D. x>-9/7) thank you for using weegy! have a blessed day(: (More)

Question

Updated 11/24/2017 4:03:44 PM

1 Answer/Comment

5(x + 1) - 3(x - 1) > -9

5x + 5 - 3x + 3 > -9

2x + 8 > -9

2x > -9 - 8

2x > -17

x > -17/2

5x + 5 - 3x + 3 > -9

2x + 8 > -9

2x > -9 - 8

2x > -17

x > -17/2

Added 11/24/2017 4:03:43 PM

This answer has been confirmed as correct and helpful.

Solve for x: 3(x - 2) = 5(x + 2)

Question

Updated 11/24/2017 4:02:03 PM

1 Answer/Comment

3(x - 2) = 5(x + 2)

3x - 6 = 5x + 10

3x - 5x = 10 + 6

-2x = 16

x = 16/-2

x = -8

3x - 6 = 5x + 10

3x - 5x = 10 + 6

-2x = 16

x = 16/-2

x = -8

Added 11/24/2017 4:02:03 PM

This answer has been confirmed as correct and helpful.

37,264,961

questions answered

There are no comments.